2000
DOI: 10.1096/fasebj.14.10.1265
|View full text |Cite
|
Sign up to set email alerts
|

Lysosome‐related organelles

Abstract: Lysosomes are membrane-bound cytoplasmic organelles involved in intracellular protein degradation. They contain an assortment of soluble acid-dependent hydrolases and a set of highly glycosylated integral membrane proteins. Most of the properties of lysosomes are shared with a group of cell type-specific compartments referred to as 'lysosome-related organelles', which include melanosomes, lytic granules, MHC class II compartments, platelet-dense granules, basophil granules, azurophil granules, and Drosophila p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
323
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 335 publications
(338 citation statements)
references
References 124 publications
(138 reference statements)
12
323
1
2
Order By: Relevance
“…Melanosomes are members of a class of tissue-specific "lysosome-related organelles" characterized by an acidic lumenal pH and the presence of some lysosomal proteins (Dell'Angelica et al, 2000;Griffiths, 2002). Among lysosome-related organelles, melanosomes represent a subclass that coexists with bona fide lysosomes in their host cells .…”
Section: Introductionmentioning
confidence: 99%
“…Melanosomes are members of a class of tissue-specific "lysosome-related organelles" characterized by an acidic lumenal pH and the presence of some lysosomal proteins (Dell'Angelica et al, 2000;Griffiths, 2002). Among lysosome-related organelles, melanosomes represent a subclass that coexists with bona fide lysosomes in their host cells .…”
Section: Introductionmentioning
confidence: 99%
“…2 AP-3 mediates sorting of transmembrane proteins to lysosomes in all cells, but cells with secretory lysosomes, including melanocytes, platelets and leukocytes, are functionally impaired. [3][4][5][6][7] Previous studies of cytotoxic T-lymphocyte (CTL) clones from a patient with HPS2 (P1) showed decreased cytotoxicity and enlarged lytic granules that failed to polarize correctly towards target cells. 5 We now provide a description of 2 further unrelated individuals (P2 and P3) with HPS2 associated with novel mutations in AP3B1.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The secretory lysosomes/primary granules of neutrophils are furnished with an array of proteins that includes hematopoietic serine proteases along with myeloperoxidase (MPO), other microbicidal proteins, and specific transmembrane proteins. 3,4 The precise functions of the hematopoietic serine proteases-neutrophil elastase (NE), cathepsin G, proteinase 3, and azurocidin-are not fully known, but all 4 are thought to be important in the innate immunity function provided by neutrophils.…”
Section: Introductionmentioning
confidence: 99%